Kinesiophobia and associated factors among people with musculoskeletal disorders in Ethiopia: a multicenter cross-sectional study - Yazachew Mekonnen; Moges Gashaw; Yohannes Abich; Mihret Dejen Takele; Samuel Teferi Chanie; Dechasa Imiru Wayessa; Sisay Deme; Alemu Kassaw Kibret (BMC Musculoskeletal Disorders)
Abstract Introduction Kinesiophobia has a major health impact on patients with Musculoskeletal disorders (MSDs) in their functional and physical activities, which leads to poor outcomes, loss of motivation, loss of mobility, and decreased quality of life. Despite the burden of kinesiophobia among MSDs, there is limited evidence about the burden of kinesiophobia in Ethiopia. Thus, this study aimed to assess the prevalence and its associated factors of kinesiophobia among MSD patients attending physiotherapy outpatient clinics. Method An institutional multi-center cross-sectional study was conducted from February to April 2023 with a sample size of 424. A systematic random sampling technique and face-to-face interviews using a structured questionnaire and chart review were used. The collected data was entered into Epi-data version 4.6.0.6 and analyzed using SPSS version 25. Binary logistic regression analysis was employed to identify the potential candidates for multivariable logistic regression with a p-value less than 0.25. Finally, multivariate logistic regression analysis was employed and variables at p < 0.05 with 95% CI were considered statistically significant contributors to kinesiophobia. Result The overall prevalence of kinesiophobia among MSD patients was 48.3% (95% CI, 43.3–53.3). Being overweight and obese BMI value (AOR = 3.98; 95% CI, 2.17–7.29), having moderate pain level (AOR = 3.31; 95% CI, 1.51–7.26), having severe pain level (AOR = 9.29; 95% CI, 3.79–22.77), physical inactivity (AOR = 3.00; 95% CI = 1.84–4.89), anxiety (AOR = 2.57; 95% CI = 1.57–4.19), and depression (AOR = 8.21; 95% CI = 3.47–19.46) were significantly associated with kinesiophobia among musculoskeletal disorder patients. Conclusion kinesiophobia is a public health burden among patients with MSDs. Nearly half of the people with MSDs had reported kinesiophobia. Being overweight and obese BMI value, pain severity level, physical inactivity, anxiety, and depressive symptoms were significantly associated with kinesiophobia. Thus, we suggest screening for kinesiophobia, be physically active, avoiding being overweight and obese, and managing depression, anxiety and pain will help to reduce the occurrence of kinesiophobia.